Different types of batteries and developing lead acid batteries - Md. Mashruf; Hossain, Tanvir (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2012.